Karakteristik Morfologi Post Larva Udang Penaeus dan Metapenaeus dari Kawasan Timur Segara Anakan Cilacap - Harditya Firdhaus; Dian Bhagawati; Kusbiyanto Kusbiyanto (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Information about the presence of post larvae in nature could indicate the specific presence of the sites used for growth and development of larvae and post larvae. This could be an alternative option to determine the diversity of shrimp in an area with the presence of post larvae. Research about species richness of post larvae phase of shrimp based on morphology characters, especially in the eastern region of Segara Anakan Cilacap is still rarely done, so it is necessary to collected basic data on the morphological characters of post larvae phase of shrimp. The purpose of this research is to knew species richness and morphological description post larvae phase of shrimp in the eastern region of Segara Anakan, Cilacap Regency, Central Java. The method used survey with a random sampling technique from the collection of the Laboratory of Animal Taxonomy, Faculty of Biology, Jenderal Soedirman University. The variables in this research were morphological performance, standar morphometric, and meristic of post larvae shrimps. The parameters observed were characters of morphological description on each post larvae phase of shrimp, ratio standard morphometric, and meristic calculation. Species richness, morphological performance, standard morphometric, and meristic data were analyzed descriptively. The results obtained were three species of post larvae of Family Penaeidae namely Penaeus indicus, P. merguiensis, and Metapenaeus ensis.